Estudo de funções utilizando Geogebra e Moodle - Almeida, Altair Portes de (Universidade Federal de São Carlos, 2014)
The concept of relationship between two sets, in particular, the real function of a real variable, is fundamental to mathematics education high school student, it is a basic object of mathematics is elementary and the modeling of many everyday problems or context of other sciences. However, one notes the difficulty of most students understand this concept; stands out, also, the difficulty of students to interpret a function by analyzing its graph in the Cartesian plane xOy. In this context, this thesis try alternative methods that can contribute to the improvement of teaching and learning theme in question. More precisely, it uses Geogebra educational software and the virtual environment Moodle learning for the study of elementary functions. In general, the resources of Geogebra, the Dynamic Geometry and Algebra, have to propitiate to student understands, the proper form, the ratings and the function representation as a curve in the plane; Furthermore, Geogebra allow guesses about the behavior of an elementary function parameters subject to variation. In turn, the use of Moodle environment allows communication and broader evaluation (between teacher-student and student-student) through, questionnaires / online tests, video lessons, discussion forums etc. This text is six classes developed with the participation of two groups (each with about 35 students) of the third year of high school. Initially, in order to detect major and several difficulties, an evaluation (presence) was made with basic issues (of different levels). The performance of these students was quantified, qualified (enjoying the most problematic conceptual topics) and then served as support for the activities - in order to reverse the reality presented and the existing student-mathematical relationship. It is noteworthy that the use of an educational software like GeoGebra already proposes a new dynamic student-teacher-mathematics. Wanted with this change that the student take a more active position on the mathematical content so that, in fact, with proper guidance of the teacher, can understand and demystify the concept of real function of a real variable.
Keywords: Educação matemática; Software educacional; Ambiente virtual; Education; Mathematics; Educational software; Virtual environment; CIENCIAS EXATAS E DA TERRA